Subcellular dynamics of the endogenous elicitor peptide AtPep1 and its receptors in Arabidopsis: implications for the plant immunity - Morea, Fausto Andres Ortiz (2015)
This work investigated the subcellular dynamics of the plant elicitor peptide AtPep1 and its interplay with plant defense responses. First, an introduction of the plant innate immunity system is provided with emphasis on pattern trigger immunity (PTI), which is based on the recognition of \"non-self\" and \"self\" elicitor molecules by surface-localized patternrecognition receptors (PRRs). Then, the Arabidopsis endogenous peptides that act as selfelicitor molecules are presented, with details on AtPep1 and its PEPR receptors. Plant endomembrane trafficking is described, encompassing endocytic pathways, clathrin mediated endocytosis (CME) and receptor-mediated endocytosis (RME). In the next chapter, we explored strategies for the in vivo study of the subcellular behavior of AtPep1; to this end, we fused the precursor protein of AtPep1 (PROPEP1) to GFP and assessed its localization. We found that PROPEP1 was associated with the tonoplast and accumulated in the vacuole, suggesting that this organelle could work as the station where PROPEP1 is stored and later released, only in a danger situation, hence initiating AtPep1. Moreover, we generated AtPep1 versions labeled with fluorescent dyes and demonstrated that this peptide could be fluorescently tagged without loss of its biological activity. In chapter 3, we combined classical and chemical genetics with life imaging to study the behavior of a bioactive fluorescently labeled AtPep1 in the Arabidopsis root meristem. We discovered that the labeled AtPep1 was able to bind the plasma membrane very quickly in a receptor-dependent manner. Subsequently, the PEPR-AtPep1 complex was internalized via CME and transported to the lytic vacuole, passing through early and late endosomal compartments. Impairment of CME compromised the AtPep1 responses. Our findings provide for the first time an in vivo visualization of a signaling peptide in plant cells, thus giving insights into its intracellular fate and dynamics. The role of the coregulatory receptor BRI1-associated kinase 1 (BAK1) in AtPep1-responses was also investigated (chapter 4). Our results confirmed that BAK1 interacts with PEPRs in a ligand-dependent manner and indicate that BAK1 modulates AtPep1 signaling and endocytosis, but that, when absent, it might be replaced by homologous SOMATIC EMBRYOGENESIS RECEPTOR-LIKE KINASE (SERK) proteins that could have additional functions during the AtPep1 signaling. Furthermore, phosphorylation events after the formation of PEPR-BAK1 complexes seem to dictate the molecular bases of AtPep1 internalization and signaling. Finally, we discussed our findings in a more general perspective, highlighting the important findings for the plant endomembrane trafficking field, the potential use of fluorescently labeled ligands as a tool to study ligand-receptors pairs, the availability of AtPep1-PEPRs as an excellent model to study endocytosis and its interplay with signaling, and the future challenges in the field.